Hubungan Container Index dengan Kejadian Demam Berdarah Dengue di Semarang - Christina Tri Restuti; Nur Endah Wahyuningsih; Hapsari Hapsari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Dengue Hemorrhagic Fever is an acute infectious disease caused by Dengue virus that has 4 serotypes, DEN-1, DEN-2, DEN-3, DEN-4. Dengue Hemorrhagic Fever is caused by multifactors: host, enviorment, and agent factors. The population of mosquito larvae also affect the occurrence of Dengue Hemorrhagic Fever can be measured its density with Container Index (CI. The aim of this study is to know the relationship of container index with Dengue Hemorrhagic Fever in Semarang.The type of this study was observational analytics using case control design. The sample was 38 cases and 38 controls. The instruments used observational sheets. Data were obtained from observation. Data were analyzed by Chi-square test and the determination of the Odds Ratio (OR). The result showed number of containers in case group were 488 units, there were container of larvae is 69 units (14,4%) and non larvae were 419 units (85,86%). While in the control group were 328 containers, there were larvae in 41 containers is 41 units (12.50%) and the non-larvae of 287 containers (87.50%) .The statistical test result if p value of Density Figure in container were larvae is = 0.490 and indicating that there is no relation between Container index with the incidence of Dengue Hemorrhagic Fever. The conclusion there is no relation of Container Index with the incidence of Dengue Hemorrhagic Fever in Semarang